Sex/Gender-Specific Imbalance in CVD: Could Physical Activity Help to Improve Clinical Outcome Targeting CVD Molecular Mechanisms in Women? - Vaccarezza, Mauro; Papa, Veronica; Milani, Daniela; Gonelli, Arianna; Secchiero, Paola; Zauli, Giorgio; Gemmati, Donato; Tisato, Veronica (2020)
In the last two decades, new insights have been gained regarding sex/gender-related differences in cardiovascular disease (CVD). CVD represents the leading cause of death worldwide in both men and women, accounting for at least one-third of all deaths in women and half of deaths in women over 50 years in developing countries. Important sex-related differences in prevalence, presentation, management, and outcomes of different CVDs have been recently discovered, demonstrating sex/gender-specific pathophysiologic features in the presentation and prognosis of CVD in men and women. A large amount of evidence has highlighted the role of sex hormones in protecting women from CVDs, providing an advantage over men that is lost when women reach the menopause stage. This hormonal-dependent shift of sex-related CVD risk consequently affects the overall CVD epidemiology, particularly in light of the increasing trend of population aging. The benefits of physical activity have been recognized for a long time as a powerful preventive approach for both CVD prevention and aging-related morbidity control. Exercise training is indeed a potent physiological stimulus, which reduces primary and secondary cardiovascular events. However, the underlying mechanisms of these positive effects, including from a sex/gender perspective, still need to be fully elucidated. The aim of this work is to provide a review of the evidence linking sex/gender-related differences in CVD, including sex/gender-specific molecular mediators, to explore whether sex- and gender-tailored physical activity may be used as an effective tool to prevent CVD and improve clinical outcomes in women.